Morbidity and mortality profile of neonates in a tertiary care centre in Tamil Nadu: a study from South India - S. A., Ravikumar; Elangovan, Harikrishnan; K., Elayaraja; K. K., Aravind Sunderavel (International Journal of Contemporary Pediatrics, 2018)
Background: Accurate data on morbidity and mortality pattern are useful for many reasons. The Perinatal and the neonatal period are so short but they are the most critical faces of human life1. It reflects the general health and the socio-biological features of the most vulnerable groups of the society, the mothers and the infants. The objectives of this study was to investigate the morbidity and mortality pattern of neonates admitted in Neonatal Intensive Care Unit (NICU) of tertiary care hospital. Methods: All the neonates admitted to NICU from July 2013 to June 2015, excluding the neonates referred and discharged against medical advice were retrospectively analysed for demographic profile, short term morbidity and outcome. Results: 3118 neonates were admitted in the study period. 57.5% were Males, 72.5% were inborn, 69% were term babies and 53.3% had normal birth weight. Important causes for morbidity were Perinatal asphyxia 490 (15.7%), Preterm/LBW 456 (14.6%), Neonatal jaundice 438 (14%) and then sepsis 402 (12.9%). The mortality rate was 10.4% with statistical significant difference between inborn and outborn babies (P<0.0001). The major causes of mortality are Respiratory syndrome 109 (33.6%), followed by birth asphyxia 82 (25.3%) and sepsis 82 (25.3%). The survival of term as well as normal birth weight babies was statistically significant over preterm (P<0.0001) and Low Birth Weight (LBW), Very Low Birth Weight (VLBW), Extreme Low Birth Weight (ELBW) neonates (P<0.0001> respectively. Conclusions: Birth asphyxia, prematurity, Jaundice and neonatal sepsis respiratory problems were major causes of both mortality and morbidity. There is need to strengthen services to address these problems more effectively.